Utilization of opefb fiber and fly ash from coal power plant reinforced recycle polypropylene for enhancement in flammability and thermal properties of composite production - Noraishah, Abdul Latip (2022)
Nowadays, the field of natural fibers-reinforced plastic composites has rapidly evolving because of environmental awareness and low economic cost with other advantages like low density and relatively high mechanical properties. However one of the major weaknesses of this system is its vulnerability to fire. Hence, this research aims to formulate a bio-composite that emphasises thermal and flammability performance by combining various waste streams as a source of recyclable raw material for fiber composite production. Combination of fly ash (FA) from industrial waste as silica-based flame retardant and biomass oil palm empty fruit bunch (OPEFB) fiber reinforced municipal solid waste, recycle polypropylene (RPP) with Maleinated polypropylene (MAPP) as stabilizer have been conducted. This study involved several phases; the first one is the alkaline pre-treatment of fiber to improve the interfacial adhesion of fiber with polymer matrix due to the loss of hydroxyl group. This process involved three different alkali solution; Sodium Hydroxide (NaOH), Potassium Hydroxide (KOH) and Aluminium Hydroxide (Al(OH)3) with 15% (w/v) concentration at 130°C and for 40 minutes where fibre to solution ratio at 1:10. Their physico-chemical and structural behaviour were studied in detail by several analyses; Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD). The best-treated fibers from the KOH treatment have been chosen then compounding by different formulation of OPEFB fiber, RPP, FA and MAPP have been done followed by molding process with hot press machine to prepare the samples. This process has represented as the second phase. The last phase involved the flammability performance through Limiting Oxygen Index (LOI) and Underwriters Laboratory 94 (UL94) analysis. Based on the result gained in the first phase, the removal of unwanted component such as lignin, pectin and hemicellulose that also responsible for flame degradation properties can be seen clearly at the peak around 1729.74